Maternal smoking during pregnancy, semen characteristics and reproductive hormone levels in men consulting for couple infertility. (1st October 2019) - Garlantézec, Ronan; Multigner, Luc; Oliva, Alejandro
Abstract: The aim of our study was to evaluate the relationship between maternal tobacco consumption during pregnancy and sperm parameters and sexual hormonal levels of their sons in adulthood. We conducted a cross‐sectional study in four medical institutions in Argentina, between June 1999 and June 2015, among male partners of couples consulting for infertility. At inclusion, a structured interview was conducted to obtain information on the basic demographic, medical, surgical and reproductive history, personal tobacco consumption and that of their parents during pregnancy. Two semen analyses at an interval of 2–4 weeks and a blood hormone evaluation (FSH, LH, prolactin, total testosterone and oestradiol) were then ordered. Analyses using multivariate models adjusted for potential confounders were performed for 537 men. Maternal tobacco consumption during pregnancy was associated with a significantly higher risk of reduced sperm count and elevated total testosterone levels. We did not find any significant association between maternal smoking and other sperm parameters nor other hormone levels. Our study adds evidence concerning the association between maternal tobacco consumption during pregnancy and reduced sperm counts of their sons in adulthood. The results showing an association between elevated total testosterone levels and maternal tobacco consumption need to be replicated.